Da comparação social à ideação suicida: o papel mediador da autoestima e de sintomas depressivos - Fernandes, Maianna Costa (2021)
Suicide is considered a serious public health issue across the world and there have been several studies devoted to identifying the factors contributing to its etiology. In the present study, we propose social comparison (i.e. the tendency people have to evaluate themselves in relation to others) as a factor associated with suicidal ideation, with this association being sequentially mediated by self-esteem and depression. In Study 1 (N = 120), a mediation analysis was carried out for testing whether the association between social comparison and suicidal ideation was mediated sequentially by self-esteem and depression. The results showed that social comparison had a negative impact on selfesteem, with subsequent higher levels of depressive symptoms and suicidal ideation. In Study 2 (N = 270), we manipulated a social comparison setting favorable to participants to investigate its effect on self-esteem and sequentially on depression and suicidal ideation. The results showed that the participants who made a positive comparison (i.e., perform better) had more positive self-esteem than those in the control condition, subsequently resulting in lower levels of depressive symptoms and suicidal ideation. In sum, our results showed that social comparison level was associated with higher levels of suicidal ideation, but this phenomenon may be inhibited by an intervention aimed at promoting favorable social comparisons, in that promotes better self-esteem that is associated with less depressive symptoms. The results may support that’s necessary to implement programs aimed at promoting self-esteem as an intervention to mitigate the suicide problem.